Grover's Algorithm Using IBM's Fake Providers - Frank Acasiete; Anderson Buarque (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
In this work we will show Grover's algorithm using Fake Providers which are images of real quantum computers to give us an idea of their behavior in the implementation in Qiskit and we will show the fidelities with respect to the quantum simulator which gives us the result closest to the analytical one.